2019
DOI: 10.1083/jcb.201901127
|View full text |Cite
|
Sign up to set email alerts
|

Imaging within single NPCs reveals NXF1’s role in mRNA export on the cytoplasmic side of the pore

Abstract: Translocation of mRNA through the nuclear pore complex (NPC) requires interactions with different NPC regions. To determine the interactions that are crucial for effective mRNA export in living cells, we examined mRNA export within individual pores by applying various types of mRNA export blocks that stalled mRNPs at different stages of transition. Focusing on the major mRNA export factor NXF1, we found that initial mRNP binding to the NPC did not require NXF1 in the NPC, whereas release into the cytoplasm did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 83 publications
4
31
0
Order By: Relevance
“…Furthermore, the interaction of Mex67 with the NPC is not modulated by the DEAD-box ATPase Dbp5. These findings are consistent with a recent report in mammalian cells (Ben-Yishay et al, 2019). Since Dbp5 is thought to impart directionality to the mRNA export process by releasing export factors form cargo, this suggests that the action of Dbp5 leads to the release of mRNA from Mex67 but not of Mex67 from the NPC.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the interaction of Mex67 with the NPC is not modulated by the DEAD-box ATPase Dbp5. These findings are consistent with a recent report in mammalian cells (Ben-Yishay et al, 2019). Since Dbp5 is thought to impart directionality to the mRNA export process by releasing export factors form cargo, this suggests that the action of Dbp5 leads to the release of mRNA from Mex67 but not of Mex67 from the NPC.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, we found that DDX19B and NXF1 share the same network of proteinprotein interactions with a high confidence value (0.884) ( Figure 5D). It was suggested that in human cells DDX19B functions on the cytoplasmic side of the nuclear pore complex and is required for the final release of mRNA from NXF1 into the cytoplasm [22]. All this evidence strongly supports a possible correlation between the cytosolic transport of the nuclear uc.8+ during the tumor and/or cell life, with a cytosolic role of this lncRNA in order to fulfill its cellular functions.…”
Section: Prediction Of Uc8+ Interactions In Bladder Cancermentioning
confidence: 82%
“…In particular, we aligned the uc.8+ nucleotide sequence to the Ensembl transcript annotation database. The deep learning analysis identified 46 sequences spread in 45 genes, with an average length of about 19 bp (in the range [17][18][19][20][21][22][23][24][25][26][27]. The results of the deep learning analysis for the subcellular localization of uc.8+ indicated a prevalence of lncRNA sequences located at nuclear sites (Figure 2A).…”
Section: In Silico Analysis Indicates That Uc8+ Has Both Nuclear Andmentioning
confidence: 99%
“…This raises interesting questions regarding the functional relationship of TPR and NXF1 at NPCs. Notably, recent reports suggest that NXF1-binding sites within the NPC are not closely adjacent to TPR and that NXF1 occupies sites on the cytoplasmic side of the NPC 42 . Consistent with this report, our findings indicate that NXF1 association with NPCs is independent of TPR, and we speculate that loss of TPR phenocopies loss of NXF1 because NXF1 operates upstream of both TPR and GANP at early steps of mRNA processing 1 .…”
Section: Discussionmentioning
confidence: 99%